Applying an integrated production system based on social manufacturing to develop a medical device. Issue 1 (March 2021) - Sari, Marti Widya; Herianto,; Dharma, IGB Budi; Tontowi, Alva Edy
Abstract: In the current Covid-19 pandemic, many manufacturing industries have been affected, including the health industry. The need for medical devices during this pandemic was very high, causing scarcity of goods on the market, and high selling prices, because most medical devices had to be imported. The concept of social manufacturing can be one way to revive the health industry in Indonesia. The purpose of this research is to develop an integrated production system through social manufacturing by involving small and medium companies and measuring the competitive level of production results from the quality side. The method used in this research is starting from literature study, field observation, production system design, product and system testing, and analysis of social manufacturing based production system test results. The results of this study are a social manufacturing-based production system for medical device products in the form of a Sanitation Chamber, and also the measurement of product quality in terms of performance (83.20), features (80.40), reliability (79.56), conformance (81.11), durability (84.67), service ability (78.33), aesthetics (81.83) and perceived quality (79.83).